Development of Phosphatized Calcium Carbonate Biominerals as Bioactive Bone Graft Substitute Materials, Part I: Incorporation of Magnesium and Strontium Ions - Ingo Sethmann; Cornelia Luft; Hans-Joachim Kleebe (Journal of Functional Biomaterials, 2018)
Synthetic materials based on calcium phosphate (CaP) are frequently used as bone graft substitutes when natural bone grafts are not available or not suitable. Chemical similarity to bone guarantees the biocompatibility of synthetic CaP materials, whereas macroporosity enables their integration into the natural bone tissue. To restore optimum mechanical performance after the grafting procedure, gradual resorption of CaP implants and simultaneous replacement by natural bone is desirable. Mg and Sr ions released from implants support osteointegration by stimulating bone formation. Furthermore, Sr ions counteract osteoporotic bone loss and reduce the probability of related fractures. The present study aimed at developing porous Ca carbonate biominerals into novel CaP-based, bioactive bone implant materials. Macroporous Ca carbonate biominerals, specifically skeletons of corals (aragonite) and sea urchins (Mg-substituted calcite), were hydrothermally converted into pseudomorphic CaP materials with their natural porosity preserved. Sr ions were introduced to the mineral replacement reactions by temporarily stabilizing them in the hydrothermal phosphate solutions as Sr-EDTA complexes. In this reaction system, Na, Mg, and Sr ions favored the formation of correspondingly substituted β-tricalcium phosphate over hydroxyapatite. Upon dissolution, the incorporated functional ions became released, endowing these CaP materials with bioactive and potentially osteoporotic properties.